Model Pengembangan Destinasi Pariwisata Pedesaan Studi Kasus: Desa Wisata Gambung Mekarsari - Nono Wibisono; Lina Setiawati; Sherly Raka Siwi Utomo Putri (P3M Politeknik Negeri Bali, 2020)
The Gambung Mekarsari Tourism Village Area, Ciwidey is one of the potential tourism villages owned by Bandung Regency. The village of Gambung Mekarsari has a stretch of natural land that is of concern and can be used as a natural tourist attraction and artificial tourism as a result of commodities, forestry, and agriculture. This potential is still not utilized and developed by the local community until now. This study aims to explore the potential that exists in the tourism village area and discover and develop a model of tourism village development that is most suitable for the natural region of Gambung Mekarsari. The constraints found in the field relate to the development of a model of a tourist village, from the aspect of attractiveness, accommodation, accessibility, and amenities. This study was analyzed by a qualitative approach with data collection carried out in two ways, namely Focus Group Discussion and in-depth interviews. Based on the review and analysis conducted on the characteristics, potential, problems in the field, the model with the Quintiple Helix approach has implications for the environment by involving five different elements; academia, related economic industries, government, media, and the community in the tourism village environment to strengthen the development of sustainable tourism.